A relação entre valores culturais e investimento direto estrangeiro (IDE) - Goraieb, Marcelo Ribeiro (2013)
The relationship between culture and Foreign Direct Investment (FDI) is a topic with extensive academic discussion, but with theoretical and empirical divergences. This paper contribute to the international business studies testing empirically the influence of culture on the FDI, supported by the theory of familiarity and psychic distance, through quantitative methodology, using Network Analysis techniques and testing multiple regressions between square matrices (Multiple Regression Quadratic Assignment Procedure - MRQAP). Thus the mathematical model tests the hypothesis that the presence of similarity in cultural values influences FDI between countries, from the perspective of social embeddedness and discussing the concept of cultural distance. Was used secondary data from IDE, the index of cultural values surveyed by Hofstede (1980) and more data from international organizations and others scientific researches. The unit of analysis is the relationship of FDI between countries in a sample of 45 which data for both FDI and cultural values index was obtained. The results shows that only the similarity of the cultural values imension Power Distance has FDI influences, and the presence of High Uncertainty Aversion negatively affect the FDI. The similarity of the cultural dimensions Individualism, Masculinity and Uncertainty Avoidance do not interfere in FDI between countries. The results shows that in one case the cultural difference meant a distance or barrier between countries. The theory of familiarity or the psychic distance is valid only for Power Distance cultural value dimension, and not for the others cultural values dimensions. The absence of attributes data is a methodological limitation. The major contributions of this study are: (1) an innovative methodology, (2) the empirical results that demonstrate the social embeddedness of economic actions, (3) the psychic distance and familiarity theories improvement, and (4) the identification of which cultural values interfere on the FDI.